Representasi Gastronomi dalam Puisi Pendidikan Jasmani dan Kesunyian Karya Beni Satryo - Muhammad Fhaqih; Muhammad Tauhed Supratman; Ria Kasanova (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
Previous studies have predominantly focused on novels and short stories, whereas the representation of food in poetry from a gastronomic perspective remains relatively underexplored. This study aims to examine the symbolic meanings of food in Pendidikan Jasmani dan Kesunyian, a poetry collection by Beni Satryo, through Claude Fischler's gastronomic perspective. The study employed a qualitative approach using qualitative textual analysis. Data consisted of words, phrases, lines, and stanzas containing food symbols, which were collected through documentation and close reading and subsequently interpreted using Fischler's Food, Self and Identity framework. The findings reveal that food symbols function not merely as culinary objects but as a symbolic system encompassing four interrelated dimensions: cultural identity, emotional experience, memory, and social relations. Culinary symbols such as pecel lele, kemangi (lemon basil), soto, sweet soy sauce, candy, and peanut sauce undergo aesthetic transformation through metaphorical language, enabling them to represent human experiences within the Indonesian cultural context. This study extends the application of Claude Fischler's gastronomic theory to contemporary Indonesian poetry by demonstrating that food symbols operate as cultural texts that simultaneously construct cultural identity, memory, emotional experience, and social relations. These findings enrich the field of literary gastronomy while offering a new perspective for the interpretation of Indonesian poetry through an interdisciplinary approach.